Pengaruh Time Budget Pressure, Audit Tenure dan Skeptisisme Profesional Auditor Terhadap Kualitas Audit : (Studi pada Kantor Akuntan Publik di Kota Padang) - Abimayu, Shadiq; Halmawati (Jurnal Nuansa Karya Akuntansi, 2026)
This study aims to determine the Effect of Time Budget Pressure, Audit Tenure and Auditor Professional Skepticism on Audit Quality. The method used in this study is a quantitative method. The population and sample in this study are Auditors working at Public Accounting Firms in Padang City with the sampling technique used is total sampling so that 45 samples are obtained. The type of data used in this study is primary data by distributing questionnaires. The analysis technique is carried out using multiple regression analysis techniques. The results of the study concluded that (1) Time Budget Pressure does not have a significant effect on Audit Quality; (2) Audit Tenure does not have a significant effect on Audit Quality; (3) Auditor Professional Skepticism has a significant effect on Audit Quality. Suggestions for further research are to be able to take samples and populations in a wide scope such as KAP in West Sumatra. The second suggestion is that further research is expected to add other variables that are not yet in this study.